Influence of bisphosphonates on oral implantology: Sodium alendronate and zoledronic acid enhance the synthesis and activity of matrix metalloproteinases by gingival fibroblasts seeded on titanium - Basso, Fernanda Gonçalves (2021)
Objective: This study aimed to assess the influence of the bisphosphonates zoledronic acid and sodium alendronate on MMP-2 and MMP-9 synthesis and activity by gingival fibroblasts seeded onto titanium substrate. Design: Titanium discs were placed in 24-well cell culture plates and gingival fibroblasts were seeded (1 × 105 cells/discs) on them using Dulbecco's Modified Eagle's Medium (DMEM) + 10 % fetal bovine serum (FBS) for 24 h. After this period, a fresh serum-free DMEM containing zoledronic acid or sodium alendronate at 0.5 μM, 1 μM or 5 μM was applied on the cells for an additional of 24 h. Serum-free DMEM and tumor necrosis factor alpha (TNF-α) were used as negative and positive controls, respectively. MMP-2 and MMP-9 synthesis and activity were determined by ELISA (Enzyme-Linked Immunosorbent Assay) and conventional/in situ zymography. Quantitative data were analyzed by one-way ANOVA and Tukey's tests (α = 0.05). The in situ zymography data were qualitatively described. Results: Despite both bisphosphonates increased the MMPs synthesis, this effect was significant higher in zoledronic acid groups. MMPs activity resembled by gelatinolytic activity was also enhanced by sodium alendronate and zoledronic acid in a similar pattern. Conclusions: Zoledronic acid and sodium alendronate increased in a dose-dependent manner MMP-2 and MMP-9 synthesis by gingival fibroblasts seeded on titanium. MMP-2 activity was up-regulated by zoledronic acid treatment.